2002
DOI: 10.1136/gut.50.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Staging of hepatocellular carcinoma: assessment of the CLIP, Okuda, and Child-Pugh staging systems in a cohort of 257 patients in Toronto

Abstract: Background: A new staging system for hepatocellular carcinoma (HCC) has recently been reported from Italy (CLIP classification). It combines Child-Pugh staging with tumour criteria: tumour morphology, portal invasion, and alpha fetoprotein levels. Aims: To validate the use of the CLIP staging in a cohort of HCC patients and compare it with Okuda staging. Patients and methods: A retrospective analysis of patients with HCC diagnosed in the Toronto General Hospital between October 1994 and December 1998. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
137
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(154 citation statements)
references
References 15 publications
12
137
1
3
Order By: Relevance
“…Levy and Sherman (2002) reported that the CLIP classification for HCC is easier to implement and more accurate than the OKUDA classification. In addition, Koike et al (2001) suggested that serum PIVKA-II level is the most useful predisposing clinical parameter for the development of portal vein invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Levy and Sherman (2002) reported that the CLIP classification for HCC is easier to implement and more accurate than the OKUDA classification. In addition, Koike et al (2001) suggested that serum PIVKA-II level is the most useful predisposing clinical parameter for the development of portal vein invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The CLIP system has been externally validated in Canadian, 34 Italian, 35 and Japanese cohorts. 19 CLIP was recently endorsed by a consensus conference on HCC staging because it was the only staging system externally validated.…”
Section: Discussionmentioning
confidence: 99%
“…Local therapies such as percutaneous ethanol injection, thermal ablation, and intra-arterial chemoembolization are less successful, 5 and less than 10% of patients with moderate disease (Okuda stage 2) survive for 3 years. 6 Immunological mechanisms are important in the surveillance of malignancy and control of tumor progression. Cytotoxic CD8 ϩ lymphocytes (CTLs) and natural killer cells are potential effector cells in the control of tumor growth, although both require CD4 ϩ T helper 1 immune responses for optimal function.…”
mentioning
confidence: 99%